2005
DOI: 10.1590/s0103-97332005000300024
|View full text |Cite
|
Sign up to set email alerts
|

Integers: irreducible guides in the search for a unified theory

Abstract: The notion of final theory results from a contrasting understanding of physical reality. Currently, different approaches aim to unify the four forces of nature and discuss whether a final theory may be possible. A key feature of a final theory is irreducibility, however this property has not been seriously exploited. In the paper we present an irreducible mathematical theory that describes physical systems in terms of formation processes of integer relations. The theory has integers and integer relations as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The figure shows that for states [2] (t ) > g [2] (t ), t 0 < t < t 8 , the third integrals are not equal f [3] (t 8 ) = g [3] (t 8 ). Thus, the states x and x 0 share two of the quantities and C(x,x 0 ) ¼ 2.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The figure shows that for states [2] (t ) > g [2] (t ), t 0 < t < t 8 , the third integrals are not equal f [3] (t 8 ) = g [3] (t 8 ). Thus, the states x and x 0 share two of the quantities and C(x,x 0 ) ¼ 2.…”
Section: Figurementioning
confidence: 99%
“….,Q k )] into the system of k Diophantine equations, as its solution, produces a system of k integer identities or relations. It is shown that the system of integer relations can be associated with a number of hierarchical structures, which can be interpreted as a result of self-organization processes of prime integer relations [1,[3][4][5].…”
Section: Figurementioning
confidence: 99%
“…In the geometric form the nonlocal correlations are represented by two-dimensional patterns that may characterize the dynamics of the parts in a strong scale covariant form. Significantly, based on the integers and controlled by arithmetic only, the self-organization processes can specify complex systems by information not requiring further explanations (Korotkikh 1999(Korotkikh , 2005.…”
Section: The Concept Of Structural Complexitymentioning
confidence: 99%
“…To address the situation we suggest an approach based on the description of complex systems in terms of selforganization processes of prime integer relations (Korotkikh 1999(Korotkikh , 2005. To measure the complexity of a system in terms of the partial order of the processes the concept of structural complexity is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…1: The figure shows that for states x = +1 − 1 + 1 − 1 − 1+1+1+1 and x ′ = −1−1+1+1+1+1+1−1 the first integrals are equal f [1] (t8) = g [1] (t8), where f = ρ mεδ (x), g = ρ mεδ (x ′ ) and m = 0, ε = 1, δ = 1. It turns out that the second integrals are also equal f [2] (t8) = g [2] (t8), but the third integrals are not f [3] (t8) = g [3] (t8). Thus C(x, x ′ ) = 2.…”
Section: Invariant Quantities Of a Complex System And Underlying mentioning
confidence: 99%